Penegakan Hukum Terhadap Polisi Yang Terlibat Dalam Peredaran Narkotika(Studi Kasus Peredaran Sabu Teddy Minahasa) - Tiara Siti N; Elwidarifa Marwenny (CV. ITTC INDONESIA, 2024)
Drug abuse cases involving public figures, including artists and officials, have become a media spotlight, highlighting that the drug problem transcends social and economic boundaries. When individuals who are supposed to be role models for society are involved in drug abuse, it underscores the urgency for more effective prevention and law enforcement measures. Combating drug trafficking is a top priority in maintaining public safety and order. A notable case is that of Teddy Minahasa, which highlights the crucial role of the police in tackling drug networks. This paper examines: 1) Legal Regulations Regarding Law Enforcement by the Police Against Police Officers Who Break the Law; 2) Law Enforcement Against Police Officers Involved in Drug Trafficking (Case Study of Teddy Minahasa's Methamphetamine Distribution). To address these issues, a normative juridical research method is used, yielding the following results: 1) Legal Regulations Regarding Law Enforcement by the Police Against Police Officers Who Break the Law, namely Articles 34-35 of Law Number 2 of 2002 concerning the Police and Articles 5, 6, and 9 of Government Regulation Number 2 of 2003 concerning the Discipline of Police Members, as well as the Criminal Code (KUHP). Oversight mechanisms are carried out both internally by the Inspectorate of General Supervision (Itwasum) and the Division of Profession and Security (Divpropam), and externally by the National Police Commission (Kompolnas), which plays an important role in enforcing discipline and ethics. Police officers involved in criminal acts are processed through general courts without any special legal immunity. Despite challenges such as strong corps culture and corruption practices, reforms continue to improve the system and increase transparency and accountability in law enforcement; 2) Law Enforcement Against Police Officers Involved in Drug Trafficking (Case Study of Teddy Minahasa's Methamphetamine Distribution), demonstrating the vital role of the police in combating destructive drug networks. Such cases not only threaten social security but also undermine the integrity of the police institution. The police must play an important role in identifying, investigating, and dismantling drug syndicates by utilizing technology and inter-agency cooperation. With public support and joint commitment, law enforcement against drug cases can become more effective, ensuring public safety and upholding the rule of law in Indonesia.